2020
DOI: 10.1186/s12870-020-02660-5
|View full text |Cite|
|
Sign up to set email alerts
|

miR168 targets Argonaute1A mediated miRNAs regulation pathways in response to potassium deficiency stress in tomato

Abstract: Background Potassium (K+) is an essential ion for most plants, as it is involved in the regulation of growth and development. K+ homeostasis in plant cells has evolved to facilitate plant adaptation to K+-deficiency stress. Argonaute1 (AGO1) is regulated by miR168 to modulate the small RNA regulatory pathway by RNA silencing complex (RISC) in tomatoes. However, the role of miR168-mediated regulation of AGO1 in the context of K+ deficiency stress in tomatoes has not been elucidated yet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…A protoplast cell‐based reporter assay further confirmed that these OsAGO1 family genes including OsAGO1c are targeted for mRNA cleavage by OsMIR168a . Our conclusion is consistent with previous studies in other plant species (Iki et al ., 2018; Li et al ., 2012; Liu et al ., 2020b; Xian et al ., 2014) and a recent study in rice (Wang et al ., 2021a). The phenotypes of the mature plants and seeds of the OsMIR168a rice mutants are also similar with the transgenic rice lines that carried the MIM168a construct (Wang et al ., 2021a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A protoplast cell‐based reporter assay further confirmed that these OsAGO1 family genes including OsAGO1c are targeted for mRNA cleavage by OsMIR168a . Our conclusion is consistent with previous studies in other plant species (Iki et al ., 2018; Li et al ., 2012; Liu et al ., 2020b; Xian et al ., 2014) and a recent study in rice (Wang et al ., 2021a). The phenotypes of the mature plants and seeds of the OsMIR168a rice mutants are also similar with the transgenic rice lines that carried the MIM168a construct (Wang et al ., 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…It regulates plant growth and development (Vaucheret et al ., 2004; Wang et al ., 2021a; Xian et al ., 2014; Zhou et al ., 2020). It has also been found to participate in plant response to abiotic stress (Li et al ., 2012; Liu et al ., 2020b) and biotic stress such as virus (Iki et al ., 2018; Varallyay et al ., 2010) and fungus (Li et al ., 2014; Wang et al ., 2021a). MIR168’s broader roles in plants can be explained by the fact that it targets Argonaute 1 (AGO1) which encodes the core component of the RISC (Mallory et al ., 2008; Vaucheret, 2008; Voinnet, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The roots are the primary source of K + uptake in plants ( Liu et al, 2020 ), but only a small proportion of the potassium present within the soil is in the form of available K + , and as such, K + deficiency has become a major global threat to sustainable agricultural planting efforts ( Römheld and Kirkby, 2010 ; Wang and Wu, 2015 ; Ye Z. et al, 2020 ). It is therefore vital that the genetics and regulation of plant low-K + stress responses be studied in detail to facilitate the development of more K + -efficient crop cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Argonaute1 (AGO1) is an RNA splicing mediator that is suppressed by miR-168 ( Qi et al, 2005 ; Xian et al, 2014 ). When exposed to low-K + stress, tomato ( Solanum lycopersicum ) plants exhibit the upregulation of SlmiR-168a and corresponding AGO1 downregulation that alters miRNA responses and bolsters K + deficiency tolerance ( Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the original publication [ 1 ] there was an incorrect reference citation. In this correction article the incorrect and correct information are listed.…”
mentioning
confidence: 99%